Developing Pictionary Game Media to Teach Speaking and Writing Skills for VII F Grade at MTsN 3 Blitar - Anfa, Yunika Lailati; Rofi'ah, Siti; Saifudin, Ahmad; Makrifah, Istina Atul (Lembaga Penelitian dan Pengabdian Masyarakat Universitas Nahdlatul Ulama Blitar, 2025)
The purpose of this project is to create an educational media in the form of a Pictionary Game to help seventh-grade students at MTsN 3 Blitar improve their speaking and writing abilities. Many students considered English difficult and uninteresting owing to traditional teaching techniques, which resulted in poor enthusiasm and confidence in utilizing the language. The researcher created and assessed the efficacy of Pictionary Game media using the ADDIE paradigm. Data gathering methods included observations, questionnaires, and pre- and post-tests. Media, instrument, and material specialists validated the product and gave it